Effects of home confinement on physical activity, nutrition, and sleep quality during the COVID-19 outbreak in amateur and elite athletes - Taheri, Morteza; Irandoust, Kadijeh; Reynoso-Sánchez, Luis Felipe; Muñoz-Helú, Hussein; Cruz-Morales, Karla Noelia; Torres-Ramírez, Raymundo; Mirmoezzi, Masoud; Youzbashi, Leila; Mirakhori, Fatemeh; Dergaa, Ismail; Vancini, Rodrigo Luiz; Mataruna-Dos-Santos, Leonardo Jose; et al. (Frontiers in Nutrition, 2023)
Introduction Despite the progress in the management of the pandemic caused by COVID-19, it is necessary to continue exploring and explaining how this situation affected the athlete population around the world to improve their circumstances and reduce the negative impact of changes in their lifestyle conditions that were necessitated due to the pandemic. The aim of this study was to analyze the moderating influence of physical activity (PA) and dietary habits on the impact of the COVID-19 pandemic experience on sleep quality in elite and amateur athletes. Materials and methods A total of 1,420 elite (40.1%) and amateur (59.9%) athletes (41% women; 59% men) from 14 different countries participated in a cross-sectional design study. Data were collected using a battery of questionnaires that identified sociodemographic data, sleep quality index, PA levels, dietary habits, and the athletes' perception of their experience during the COVID-19 pandemic. Means and standard deviations were calculated for each variable. The analysis of variances and the correlation between variables were carried out with non-parametric statistics. A simple moderation effect was calculated to analyze the interaction between PA or dietary habits on the perception of the COVID-19 experience effect on sleep quality in elite and amateur athletes. Results The PA level of elite athletes was higher than amateur athletes during COVID-19 (p < 0.001). However, the PA level of both categories of athletes was lower during COVID-19 than pre-COVID-19 (p < 0.01). In addition, amateurs had a higher diet quality than elite athletes during the pandemic (p = 0.014). The perception of the COVID-19 experience as controllable was significantly higher (p = 0.020) among elite athletes. In addition, two moderating effects had significant interactions. For amateur athletes, the PA level moderated the effect of controllable COVID-19 experience on sleep quality [F(3,777) = 3.05; p = 0.028], while for elite athletes, the same effect was moderated by dietary habits [F(3,506) = 4.47, p = 0.004]. Conclusion Elite athletes had different lifestyle behaviors compared to amateurs during the COVID-19 lockdown. Furthermore, the relevance of maintaining high levels of PA for amateurs and good quality dietary habits by elite athletes was noted by the moderating effect that both variables had on the influence of the controllable experience during the COVID-19 pandemic on sleep quality.